Agronomic Performance of IPB’s Red Chili Pepper (Capsicum annuum L.) Lines in Different Environments in Bogor, West Java, Indonesia - Vicente, Tobias Moniz; Wahyu, Yudiwanti; Syukur, Muhamad; Setiawan, Asep (Department of Agronomy and Horticulture, IPB University, 2022)
Our study aims to determine the agronomic performances of the red chili pepper genotypes developed by the IPB University as compared to the existing commercial varieties. The study was conducted from June 2019 to April 2020 in the Leuwikopo and Tajur experimental fields, IPB University, Bogor, West Java, Indonesia. Leuwikopo and Tajur location differs in the soil type and environments. The experiments at Leuwikopo were conducted twice, once during the dry season, and once during the rainy season. The experiments were set up in a completely randomized block design with a single factor, i.e. sixteen red chili pepper lines, replicated three times in three different environments. The 11 lines evaluated were F8120005-141-16-35-1-3, F8120005-141-16-35-1-4, F8120005-141-16-35-7-1, F8120005-241-2-9-4- 4, F7120005-120-7-1-7-8-1-2, F6074-7-4-2-1, F4074136-2-3, F474077-1, F474035-2-1, F474035-2, F4136074-1-4; these lines were compared to five commercial chili varieties, “Laris”, “Gada” F1, “Kastilo” F1, “Anies IPB”, “Seloka IPB”. Measurements were conducted on time to harvest, fruit length, fruit diameter, weight per fruit, number of fruits per plant, fruit weight per plant, and productivity. The results showed that the curly and large red chili pepper genotypes had similar agronomic performances to the control curly variety “Laris” and “Kastilo” F1, and and “Anies IPB”, “Seloka IPB”, or “Gada” F1 as control variety for the large chili. Our study demonstrated that all large and curly red chili pepper lines developed in IPB University have excellent potentials to be commercialized into superior varieties.